The Canadian modernists meet - Irvine, Dean, 1971- (Re-appraisals, Canadian writers ;, 2005)
"The Canadian Modernists Meet is a collection of new critical essays on major and rediscovered Canadian writers of the early to mid-twentieth century. F.R. Scott's well-known poem "The Canadian Authors Meet" sets the theme for the volume: a revisiting of English Canada's formative movements in modernist poetry, fiction, and drama. As did Scott's poem, Dean Irvine's collection raises questions - about modernism and antimodernism, nationalism and antinationalism, gender and class, originality and influence - that remain central to contemporary research on early to mid-twentieth century English Canadian literature." "The Canadian Modernists Meet is the first gathering of its kind: a meeting of literary critics, textual editors, biographers, literary historians, and art historians whose collective research contributes to the study of modernism in Canada. The collection stages a major reassessment of the origins and development of modernist literature in Canada, its relationship to international modernist literatures, its regional variations, its gender and class inflections, and its connections to visual art, architecture, and film. It presents a range of scholarly perspectives, drawing upon the multidisciplinarity that characterizes the international field of modernist studies."--Jacket